The Fuzzy Set Method in the Studies on the Multilevel Political System of the European Union - Ruszkowski, Janusz (2019)
The political system of the European Union is unique and difficult to define. This presents significant problems to researchers attempting to clarify this phenomenon by means of conventional research methods. Thus, it seems necessary to start the search with other tools that will allow the exploration of the nature of this phenomenon. Such an unconventional instrument is the fuzzy set method which has been used in logics, geometry and mathematics and which accumulates both a qualitative and a quantitative approach. When applied in the studies on the multi-level political system of the EU, it reveals phenomena that could not be seen when using conventional methods. One of the most important effects of this method exists in the fuzzy levels of the EU political system situated among the traditional (crisp) levels (regional, national and supranational).